PERAN DUKUNGAN SOSIAL DALAM MENCEGAH ANEMIA PADA IBU HAMIL TRIMESTER 2 DI KOMUNITAS KELAS IBU HAMIL PUSKESMAS KARANGDORO - Anugrah Wulandari; Asnia Ananta; Aulia Eka Oktaviana; Widya Mariyana (STIKES Telogorejo Semarang, 2024)
Anemia in pregnant women, especially during the second trimester, is a health issue that can have negative impacts on both the mother's and the fetus's health. One of the factors that can prevent anemia is the social support received by pregnant women from family, husbands, friends, and healthcare providers. This study aims to identify the role of social support in preventing anemia in pregnant women during the second trimester in the Pregnant Women's Class community at Karangdoro Health Center. The research design used is quantitative with a descriptive approach, involving 33 pregnant women in their second trimester registered at Karangdoro Health Center from January to March 2024. Data was collected using a questionnaire to measure the level of social support and a hemoglobin test to determine anemia status. The two variables were then tested using chi-square to determine the role of social support in preventing anemia in pregnant women. The results of the study show that 66.7% of pregnant women experienced mild anemia, 21.2% had moderate anemia, and 12.1% were not anemic. Statistical analysis indicates a significant relationship between the social support received by pregnant women and the prevalence of anemia (p < 0.05). Pregnant women who received more intense social support tended to have higher hemoglobin levels and were less likely to experience anemia. Social support, which includes nutritional information, motivation, and reminders for health checks, was proven to increase pregnant women's awareness of maintaining their health and consuming nutritious food. This study suggests that Karangdoro Health Center strengthen the pregnant women's class program by involving families and the community more actively in providing social support.